Development of Pop-Up Book Media to Improve The Ability of Mathematical Understanding of Addition and Subtraction Materials in Students with Mild Mental Disabilities at SLB Negeri Mandiraja Banjarnegara Regency - Umu Reni Anastaqia; Arin Rustianto (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
Mathematical understanding ability is a basic and most important ability in learning mathematics so that it must be mastered by students. This is because each mathematical concept has its own relationship. Students with mild mental retardation at SLB Negeri Mandiraja have low mathematical understanding ability. This is because learning still uses media that does not adapt to the characteristics of mentally retarded students so that students find it difficult to understand learning. Therefore, learning media has a very important role in supporting learning including improving students' mathematical understanding ability. Therefore, the purpose of this study is to develop valid and effective Pop-Up Book media to improve students' mathematical understanding ability. The method used in this study is Research and Development (R&D). The results of this study indicate that the media developed is valid and interesting to use with a percentage of material expert validation of 80%, media expert validation of 96.7%, trials by mathematics teachers of 86%, and field trials of 90.2%. In addition, the Pop-Up Book learning media was also declared effective with an N-Gain score of 0.781. This study concludes that Pop-Up Book media is effective in improving the mathematical understanding abilities of students with mild mental retardation.